United States : Selected Issues. (IMF Staff Country Reports; Country Report, 2000)
This Selected Issues paper focuses on the adoption of new technology and globalization in the United States of America, and assesses the change in the productivity growth and revised estimates, the developments in the labor market, equity prices, and the technology boom. The paper analyzes how the monetary policy influences economic conditions in emergency markets; reviews the developments in financial consolidation; discusses the key provisions contained in the Gramm-Leach-Bliley (GLB) Act, the implications of the GLB Act for financial consolidation, and regulatory and supervisory practices.